Sosialisasi Pengolahan Sampah Anorganik kepada Siswa Kelas VIII SMP Negeri 7 Mataram - Tabroni, Muhammad; Nyoman Lolly Tirta Sudibya; Dasusmi, Krisna Jivani; Laila Fadila; Mubdiya Diniyati Shobah; Vetty Sugiarty; Barinta Nur Respasari; Tabita Wahyu Triutami (Pendidikan Matematika, FKIP Universitas Mataram, 2024)
Inorganic waste is waste that is difficult to decompose, for example, plastic snacks, plastic bags, plastic/glass bottles, etc. Handling inorganic waste requires attention because wise methods are needed to manage and recycle inorganic waste properly. Because in reality, inorganic waste is the largest waste produced by humans. This can be seen from the accumulation of plastic waste around humans. Therefore, this activity aims to provide students with direct knowledge of how to process inorganic waste into valuable products. The method used in this journal is a qualitative descriptive method. This activity was carried out in class VIII I of SMP Negeri 7 Mstaram starting from 2 – 26 October 2023. The total number of students in this class is 40 students. The method of implementing this activity includes several stages, namely the problem identification stage, the action planning stage, the action implementation stage, and the final stage is turning around the results and actions. The products produced from processing this inorganic waste are handicrafts such as pencil cases, flower vases, pots, cars, and so on. Then the students' handicrafts were packaged and displayed. It is hoped that this activity can continue to be carried out and developed by the school to improve the quality of learning and improve student performance in processing and utilizing inorganic waste effectively and efficiently.